Profile of pre-service teachers’ computational thinking abilities based on gender - Bettri Yustinaningrum; Nur Ainun Lubis (State Islamic University of North Sumatra, 2026)
Computational thinking is an essential competency for pre-service teachers to meet the challenges of the Fourth Industrial Revolution and Society 5.0. As future elementary school teachers, students enrolled in the Madrasah Ibtidaiyah Teacher Education Program (Pendidikan Guru Madrasah Ibtidaiyah/PGMI) need to develop computational thinking skills because they will be responsible for fostering students’ learning and problem-solving abilities. However, there is still a lack of in-depth qualitative studies examining the computational thinking processes of male and female pre-service teachers based on the computational thinking framework proposed by Jeannette Wing. Therefore, this study aimed to describe the computational thinking abilities of PGMI pre-service teachers from a gender perspective. This study employed a qualitative descriptive approach. Two participants, NS and DA, were selected through purposive sampling. Data were collected using the 2019 Bebras test, interview protocols, and observation sheets. The findings revealed that both participants demonstrated similar computational thinking abilities. In solving the two Bebras tasks, both participants successfully demonstrated all four computational thinking components, namely decomposition, pattern recognition, abstraction, and algorithmic thinking.